Estrogen Metabolite 2-Methoxyestradiol Attenuates Blood Pressure in Hypertensive Rats by Downregulating Angiotensin Type 1 Receptor - Zhang, Yong; Ogola, Benard O.; Iyer, Laxmi; Karamyan, Vardan T.; Thekkumkara, Thomas (Frontiers in Physiology, 2022)
The therapeutic potential of 2-Methoxyestradiol (2ME2) is evident in cardiovascular disease. Our laboratory has previously demonstrated the mechanism involved in the 2ME2 regulation of angiotensin type 1 receptor (AT1R) in vitro. However, 2ME2 regulation of angiotensin receptors and its effects on blood pressure (BP) and resting heart rate (RHR) are uncertain. In this study, male and female Wistar-Kyoto (WKY) rats infused with angiotensin II (65 ng/minute) and male spontaneously hypertensive rats (SHR) were surgically implanted with telemetric probes to continuously assess arterial BP and RHR. In both male and female WKY rats, 2ME2 treatment (20 mg/kg/day for 2 weeks) resulted in a significant reduction of Ang II-induced systolic, diastolic, and mean arterial BP. Moreover, significant weight loss and RHR were indicated in all groups. In a separate set of experiments, prolonged 2ME2 exposure in male SHR (20 mg/kg/day for 5 weeks) displayed a significant reduction in diastolic and mean arterial BP along with RHR. We also found downregulation of angiotensin receptors and angiotensinogen (AGT) in the kidney and liver and a reduction of plasma Ang II levels. Collectively, we demonstrate that 2ME2 attenuated BP and RHR in hypertensive rats involves downregulation of angiotensin receptors and body weight loss.